Peningkatan Public Speaking melalui Metode Bermain Peran sebagai Pemandu Wisata Virtual Museum pada Pembelajaran Pendidikan Pancasila - Agni Rizqiawan; Yan Amal Abdillah (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study aims to improve students ' public speaking skills through the role-playing method as a tour guide at the Sumpah Pemuda Museum based on a virtual museum 360-degree video. This research uses an experimental method with a pre-experimental one group pretest-posttest design model. The research sample was students of class X Pemasaran 1 SMK Negeri 1 Batang with a total of 28. The data collection technique used was observation and questionnaire which was then analyzed using descriptive and inferential statistical analysis techniques. The results showed an increase from before treatment or treatment and after treatment. The results of descriptive statistics obtained the average value of the pretest was 67.86 and the average value of the posttest was 81.29. Furthermore, the results of the paired sample t-test analysis showed a significance value of 0.000, which means that the Sig (n) value <0.05. The N-Gain test obtained an average value of 0.4308. So it is concluded that the role-playing method as a virtual museum tour guide using 360-degree video has an effect in improving students' public speaking skills.